A new species of the genus Megophrys (Amphibia: Anura: Megophryidae) from Hunan, China - Wang, Lu; Deng, Xuejian; Liu, Yong; Wu, Qianqian; Liu, Zhao (Zootaxa, 2019)
We describe a new species of Megophryidae frog, Megophrys shunhuangensis sp. nov., from Hunan Province, Southern China. It can be distinguished from other known species in the subgenus Panophrys by morphological characters, bioacoustic data and a molecular divergence in the mitochondrial 16S rRNA gene similar to that found among other species of Panophrys. M. shunhuangensis sp. nov. is characterized by a relatively small body size, with adult females measuring 37.6 mm and adult males measuring 30.3–33.6 mm in snout to vent length; maxillary teeth present, vomerine teeth absent; tongue smooth, not notched behind; hindlimb slender, heels overlapping, tibio-tarsal articulation reaches forward between the nasal and tip of snout. Molecular phylogenetic analyses also show that M. sp. 6 from (Mao’er Shan, China) from Chen et al. (2017) and M. sp. 24 (Anjiangping and Mao’er Shan, China) from Liu et al. (2018) may be the same species as M. shunhuangensis sp. nov., we consequently speculate that the new species also distributed in Anjiangping and Mao’er Shan, China. At present, the genus Megophrys contains 85 species of which 48 species are distributed in China, and 30 belong to the subgenus Panophrys.